Optical Property Stability of Light-Cured versus Precured CAD-CAM Composites - A. C. M. Andrade; A. B. Borges; E. C. Kukulka; S. E. Moecke; N. Scotti; A. Comba; C. R. Pucci; C. R. G. Torres (Hindawi Limited, 2022)
Objective. The aim of this study was to evaluate the optical property changes after staining of precured (PC) and light-cured (LC) composites. Materials and Methods. Specimens were prepared using different LC composites (GrandioSO-Voco, Filtek Z350-3M/ESPE, Opallis-FGM, and Kalore-GC) and four PC blocks (Grandio Blocs-Voco, Lava Ultimate-3M ESPE, Brava Block-FGM, and Cerasmart-GC) from the same manufacturers (n = 20). Baseline color, gloss, translucency, and fluorescence were evaluated. The staining protocol was performed for 15 days, and the final optical properties were reevaluated. Results. The changes in each property were calculated (ΔGloss, ΔTranslucency, ΔFluorescency, ΔE ∗ 00). Data were analyzed by ANOVA and Tukey's test (α = 5%). Changes in all properties were observed after staining for all materials, with darkening and reduction of gloss, fluorescence, and translucency. Nonsignificant differences were observed between the light-cured and precured materials of the same manufacturer for ΔG and ΔT, but significant differences existed for ΔF and ΔE ∗ 00. For ΔF, the only significant differences were observed between Brava Block and Opallis (smaller). For ΔE ∗ 00, only the light-cured composites GrandioSO and Z350 showed significantly less change than the corresponding blocks. Precured composites were affected the same way as light-cured ones by the staining in relation to the reduction of gloss and translucency. Conclusion. A higher reduction in fluorescence was observed for only one brand of block and was similar for the others. The two brands of light-cured materials showed less staining, while for the others, the staining was similar. The effects of staining vary according to the composite formulation.